Differential Roles of the Pseudomonas aeruginosa PA14 rpoN Gene in Pathogenicity in Plants, Nematodes, Insects, and Mice - Hendrickson, Erik L. (American Society for Microbiology, 2001)
We cloned the rpoN (ntrA, glnF) gene encoding the alternate sigma factor ς(54) from the opportunistic multihost pathogen Pseudomonas aeruginosa strain PA14. A marker exchange protocol was used to construct the PA14 rpoN insertional mutation rpoN::Gen(r). PA14 rpoN::Gen(r) synthesized reduced levels of pyocyanin and displayed a variety of phenotypes typical of rpoN mutants, including a lack of motility and the failure to grow on nitrate, glutamate, or histidine as the sole nitrogen source. Compared to wild-type PA14, rpoN::Gen(r) was ca. 100-fold less virulent in a mouse thermal injury model and was significantly impaired in its ability to kill the nematode Caenorhabditis elegans. In an Arabidopsis thaliana leaf infectivity assay, although rpoN::Gen(r) exhibited significantly reduced attachment to trichomes, stomata, and the epidermal cell surface, did not attach perpendicularly to or perforate mesophyll cell walls, and proliferated less rapidly in Arabidopsis leaves, it nevertheless elicited similar disease symptoms to wild-type P. aeruginosa PA14 at later stages of infection. rpoN::Gen(r) was not impaired in virulence in a Galleria mellonella (greater wax moth) pathogenicity model. These data indicate that rpoN does not regulate the expression of any genes that encode virulence factors universally required for P. aeruginosa pathogenicity in diverse hosts.